Preservation of sexual function when relieving benign prostatic obstruction surgically: can a trade-off be considered?. Issue 1 (January 2016) - Chung, Amanda; Woo, Henry H.
Abstract : Purpose of review: There is increasing interest among men who require benign prostatic obstruction (BPO) surgery for treatment, which also preserves sexual function. Transurethral resection of the prostate (TURP) impacts sexual function; some novel treatments claim to preserve it. Concerns exist among urologists however: can sexual function truly be preserved whilst achieving the same magnitude and durability of lower urinary tract symptoms (LUTS) improvement? Can a trade-off be considered? This review examines the literature over the recent 12–18 months to determine whether surgical BPO treatments can truly preserve sexual function whilst effectively treating LUTS–BPO. Recent findings: TURP negatively impacts erectile function, but laser prostatectomy does not. Established cavitating BPO surgeries (TURP and laser prostatectomy) tend to have high rates of an ejaculation. Ejaculation sparing modifications to existing cavitating surgeries show promising outcomes in early reports. Prostatic urethral lift preserves ejaculatory and erectile function, whilst significantly improving LUTS in short to medium-term follow-up. WAVE (Rezum System) appears promising for LUTS treatment whilst preserving sexual function in early studies. Summary: Pathophysiological mechanisms underlying the association between LUTS–BPO and sexual function are not entirely understood. Whilst novel procedures can preserve both antegrade ejaculation and erectile function, long-term efficacy in maintaining benefits to LUTS is to be established. Although standard cavitating surgeries are associated with significant anejaculation, new modifications to surgical technique may offer promising solutions.